The Role of Engagement on the Relationship Between Motivation and Future Volunteering Intention: The Case of the 30th Southeast Asian Games - Roel S. Agustin (Journal of Social Entrepreneurship Theory and Practice, 2021)
Volunteering in major sporting events has become a trend, for sports volunteers are considered one of the most valuable human resources to the event. This study intended to establish a structural model that describes the role of engagement on the relationship between motivation and future volunteering intention in a sporting event. It aimed to provide implications for organizers and volunteer coordinators to effectively retain experienced volunteers and motivate them to engage in future events. The participants of the study were the 168 sport event volunteers at the 30th SEA Games – Clark Cluster. The data were analyzed using Structural Equation Modeling to test the causal relationships of the variables. The study found that skill enrichment, privileges of volunteering, and social enrichment positively influenced volunteer engagement, while community contribution, skill enrichment, positive life experiences, and volunteer engagement positively influenced intention to volunteer in the future. The study concluded that volunteer engagement has no mediating role between motivation and future volunteering intention. Sport event organizers must manage volunteers by satisfying their personal and social needs toward volunteering and providing moral support through proper work design, efficient training, and an inclusive working environment to keep them engaged and committed in sustaining their volunteering act.